Reactivity of an organism at hypertrophic skin scars - M. V. Kobets (Scientific Сentre for Family Health and Human Reproduction Problems, 2014)
The aim of the research was to assess the reactivity of female organism with hypertrophic scars. 42 women of 16-35years were examined on the 5-7th day of the menstrual cycle, 17 of them had normotrophic and 25 - hypertrophic scars. The quality of scars (according to the clinical and morphological characteristics), white blood cells, blood lipids, hormonal and immune status were assessed. Non-parametric Mann - Whitney U-test and discriminant analysis were used at statistical processing of the results. Average values and standard deviations were also calculated for interpreting the results of quantitative indications. As the result of discriminant analysis the most informative indicators of reactivity of an organism that allow to differentiate patients of the studied groups were defined for patients with normotrophic and hypertrophic scars. It was concluded that the imbalance of steroid hormones (progesterone, cortisol, testosterone, estrogen) was important in the etiopathogenesis of hypertrophic scars.